Pengelolaan Hutan Berbasis Kearifan Lokal di Hutan Lindung Pong Dode, Kecamatan Lamba Leda Selatan, Kabupaten Manggarai Timur - Maria Heldiana Jemian; Nixon Rammang; Pamona Silvia Sinaga; Lusia Sulo Marimpan (Journal of Innovative and Creativity, 2025)
Forest management is not solely the responsibility of the government; it is also the duty of the community to preserve the forest while improving their own welfare. One of the principles in forest protection and management is the utilization of local community wisdom. Local wisdom is a key asset for communities in advancing themselves without disrupting the social balance that harmonizes with the surrounding natural environment. The application of local wisdom can be found in various regions, such as in forest areas located in East Manggarai Regency, South Lamba Leda Subdistrict. Local wisdom in Mano Village is used to protect and preserve the forest. The purpose of this study is to identify the forms of local wisdom possessed by the community in managing the Pong Dode Protected Forest and to understand the impact of the application of local wisdom in managing the Pong Dode Protected Forest. This research uses a qualitative method with data collection techniques through interviews, observation, and documentation. The results of this study show that there are two forms of local wisdom: prohibitions and invitations. Local wisdom has a positive impact on the preservation of the Pong Dode Protected Forest, as it instills a fear among the community of damaging the forest and its ecosystems.